Pengembangan Media Pembelajaran Untuk Matakuliah Statistika - Nujmatul Laily; Sulikah Sulikah (Jurnal Pendidikan Ekonomi (JUPE), 2022)
The Covid-19 pandemic causes many problems in online learning. The number of problems faced by students in statistics courses motivates this research. The purpose of this research is to develop and to produce a product in the form of learning videos for Statistics courses. This study used Borg & Gall development model which was modified into 7 stages, consists of need analysis, design and development, validation, revision I and trials. Data collection methods used validation sheets and questionnaire which were analysed descriptively. The research developed learning media that has been validated using expert judgment validation technique. The results showed that the learning video is valid/feasible to use as alternative media for Statistics course.